Embedded computing techniques for remote mobile video surveillance systems - ﻿Nirmala Ramakrishnan (2017)
Unmanned aerial vehicles (UAVs) equipped with cameras are increasingly being deployed for performing vision-based wide area surveillance with minimal human intervention. Existing techniques employing global motion estimation (GME) for automatic surveillance are typically complex and compute-intensive. In this thesis, low-complexity techniques for the key functional blocks of the GME, namely, corner detection, feature tracking and robust estimation have been proposed. The proposed techniques are capable of adapting to varying image content, camera motions and moving targets, thereby making them suitable for real-time processing of aerial videos on resource-limited UAVs.